Residential Segregation by Skin Color: Brazil Revisited - Rubia da Rocha Valente; Brian J. L. Berry (Latin American Research Review, 2020)
This article examines residential segregation by skin color in forty of the largest metropolitan areas in Brazil, using census tract data from the 2010 Brazilian census. Residential dissimilarity among whites, browns, and blacks is moderate to low by US standards, and residential segregation correlates positively with socioeconomic status. By contrasting our findings with results from the 1980 Brazilian census, we observe that in thirty years, residential segregation decreased significantly in many metropolitan areas, particularly white-brown and brown-black dissimilarities. We speculate as to why these changes should have occurred.   Resumo Este artigo examina a segregação residencial por raça em quarenta das maiores áreas metropolitanas do Brasil, usando dados do setor censitário do censo Brasileiro de 2010. A dissimilaridade residencial entre brancos, pardos e negros é moderada a baixa pelos padrões dos EUA, e a segregação residencial se correlaciona positivamente com o status socioeconômico. Ao contrastar nossos resultados com o do censo Brasileiro de 1980, observamos que, em trinta anos, a segregação residencial diminuiu significativamente em muitas áreas metropolitanas, particularmente nas dissimilaridades branco-pardo e pardo-negro. Especulamos os motivos pela qual essas mudanças ocorreram.